Association Between Self-Reported Food Preferences and Psychological Well-Being During Perimenopausal Period Among Chinese Women - Wu, Tingting; Hou, Xiaorong; Zhang, Fan; Sharma, Manoj; Zhao, Yong; Shi, Zumin (Frontiers in Psychology, 2020)
Objective:This study was sought to assess the association between these two variables in Chinese women who were in perimenopausal period and whether the association is different between urban and rural areas. Methods: This is a longitudinal study of 3059 women in perimenopausal period attending the China Health and Nutrition Survey during 2009 and 2011. Preference for five kinds of food were assessed in face-to-face interviews and the PWB was measured by scoring three self-reported questions with a total score of 15. The multilevel mixed-effects linear regression was presented to assess the longitudinal association between food preference and PWB scores. In fully adjusted models, those who showed the dislike for fruits and those who showed the like for sweetened beverages had regression coefficient (95% CI) for the PWB score of -1.26, (−2.21–0.321) and 0.66 (0.20–1.11) respectively. The same results were found only among participants in urban areas, with beta coefficient ranging from -2.61(95% CI = -4.83, -0.39) for dislike fruit to 1.02(95% CI = 0.09,1.95) for like sweetened beverages. PWB score was negatively associated with the dislike for fruit and was positively associated with the preference for sweetened beverages and it was stronger among participants from urban areas. The longitudinal data indicate that the PWB score of perimenopausal women can be improved by increasing the intake of fruit and sweetened beverages appropriately.